2001
DOI: 10.1016/s0377-1237(01)80127-1
|View full text |Cite
|
Sign up to set email alerts
|

Hysteroscopy in Postmenopausal Bleeding

Abstract: The purpose of the present study was to evaluate the utility of hysteroscopy as a diagnostic tool in cases of postmenopausal bleeding, The study includes 42 cases presenting with postmenopausal bleeding on which hysterscopy was performed using rigid hysteroscope (CIRCON) with glycine 1.5% as the distension medium. In 17 of the 42 cases positive hysteroscopic findings were noted which included 2 cases of endometrial carcinoma, 2 cases of postmenopausal endometritis, 4 cases of endometrial polyp, 5 cases of endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…6 The availability of hysteroscopy for guiding endometrial biopsy leads to almost 100% accuracy in the diagnosis of endometrial neoplasia and its precursors. 7 The use of blind endometrial sampling can be inaccurate in diagnosing some pathologies, especially in cases of localized pathologies such as endometrial polyps, submucous myomas, and focal endometrial abnormalities including adenocarcinoma 8 PMB is a common clinical condition with an incidence of 10% immediately after menopause. 9 the incidence of bleeding appears to decrease over time as reported by Astrup and Olivarius who found that the incidence of bleeding fell from 409/1000 person-years immediately in the first year of menopause to 42/1000 person-years more than three years after menopause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The availability of hysteroscopy for guiding endometrial biopsy leads to almost 100% accuracy in the diagnosis of endometrial neoplasia and its precursors. 7 The use of blind endometrial sampling can be inaccurate in diagnosing some pathologies, especially in cases of localized pathologies such as endometrial polyps, submucous myomas, and focal endometrial abnormalities including adenocarcinoma 8 PMB is a common clinical condition with an incidence of 10% immediately after menopause. 9 the incidence of bleeding appears to decrease over time as reported by Astrup and Olivarius who found that the incidence of bleeding fell from 409/1000 person-years immediately in the first year of menopause to 42/1000 person-years more than three years after menopause.…”
Section: Discussionmentioning
confidence: 99%
“…diabetes, obesity, nulliparous, with late onset of menopause) 4 Hysteroscopy is a valuable diagnostic tool with high specificity for diagnosing intra-cavitary lesions and endometrial conditions in abnormal uterine bleeding (AUB) evaluation including PMB. 5 The aim of this study was to evaluate different hysteroscopic findings in women with PMB and its correlation with histopathological findings in early and late postmenopausal women. Another aim was to evaluate the impact of years of clinical experience on accuracy of hysteroscopic diagnosis of endometrial cancer…”
mentioning
confidence: 99%
“…3 So, the combination of hysteroscopy with hysteroscopy directed biopsy potentially serves a diagnostic and therapeutic purpose. 9,10,11 Several studies had been done for evaluation of endometrium in postmenopausal bleeding and most of the studies showed high sensitivity, specificity, positive predictive value, negative predictive value of hysteroscopy for diagnosis of endometrial pathology.…”
Section: Guideline For Post-menopausal Bleeding Assessmentmentioning
confidence: 99%